ANALISIS TEKNIK RAGAM DIALOG DIAGNOSIS PENYAKIT BERBASIS SPK DENGAN SEMPLS - Jihadil Qudsi; Jian Budiarto; Sandi Justitia Putra (Jurnal Nasional Teknologi dan Sistem Informasi, 2018)
Decision support systems, commonly called DSS (or SPK in Bahasa), in medical used to diagnose illness. But within its implementation these systems are not used optimally. The main cause is the interface of the systems that is not accordance with the user wants. Three interface designs layouts were proposed for the phase of history and physical examination and two interface designs layouts for investigations to be assessed by the respondents. Based on the results of the questionnaires selected by respondents, statistical tests were performed to determine the value of the use of interface design based on the Technology Acceptance Model (TAM) and modified TAM. The statistical methods used to examine the effect of variables on TAM and modified TAM i.e. the Structural Equation Modeling Partial Least Square (SEM PLS) method. The results of this study indicate that the respondents’ choice in the TAM and modified TAM model for the history and physical examination is the same as the based filling system. While for the supporting stage there are differences of respondent choice on TAM model with choice of graphical interaction system and on modified TAM model with windowing system option.